ANALYSIS OF LONG BEANS (Vigna Sinesis. L) FARMING IN AMBULU SUBDISTRICT OF JEMBER REGENCY - Putra, Avian Pratama; Hadi, Syamsul; Widjayanti, Fefi Nurdiana (Universitas Muhammadiyah Jember, 2019)
Long beans are horticultural products that have good economic prospects, because they have a growing number of requests. While on the other hand the economic prospect has not been supported by a better level of farm management and adequate product selling value. This study aims to (1) calculate the benefits of long bean farming in Ambulu District, Jember Regency, (2) to calculate the efficiency of using long bean farming costs in Ambulu District, Jember Regency, (3) to analyze the factors that influence the production of peanut farming length in Ambulu District, Jember Regency. This study uses descriptive methods and surveys with deliberate regional selection, where Ambulu District, Jember District was chosen as the sample location. Sampling was carried out in proportioned random sampling, data obtained from interviews with farmers and related institutions. Data analysis methods used are profit analysis, RC-ratio, and multiple non-linear regression. This study concluded that: (1) long bean farming in Ambulu District, Jember Regency is beneficial. The average per hectare of profits obtained by farmers is IDR 7,702,100 in one production process (3-3.5 months). (2) the results of R / C on long-bean farming per hectare obtained 1,416 so that long bean farming has been efficient in using costs. (3) Production factors that show significant influence on long bean farming in Ambulu District, Jember Regency consist of land area, amount of fertilizer and number of labor. While the factors of seed production, and pesticides have a non-significant effect on the production of long bean farming in Ambulu District, Jember Regency.